Challenges in the establishment of a rare plant species monitoring program using community science volunteers - David J. Gibson; Christopher D. Benda; Ingrid Felsl; Gretel Kiefer (Ecological Solutions and Evidence)
Abstract Community science programs enable the collection of large amounts of important data and enhance the appreciation of science among members of the public. However, there are challenges in the establishment of successful community science programs. We report the challenges associated with the recent establishment of a community science program to monitor rare plants in the geographically diverse southern Illinois, USA region. Over the first 3 years, our program has been successful in the collection of over 250 monitoring records for rare species through the recruitment of a group of passionate volunteers. However, our volunteers are predominantly middle‐income, college educated, white females who are not representative of the population at large of the region. We propose a recruitment strategy to broaden the diversity of our volunteers by better engaging community members who are not typically involved with plant monitoring but are interested in hiking, walking in natural areas, gardening, and restoration activities, and others who would like the opportunity to collaborate with scientists and researchers in addressing an environmental issue. Practical implication: Community science plant monitoring programs face challenges in recruitment, retention, remoteness of field sites and data quality. Addressing these challenges through targeted recruitment strategies aimed at reducing structural and cultural barriers to participation, along with frequent program assessment, is necessary to enhance the success of these programs.